Controversia entre el impuesto predial, la Propiedad y la Posesiòn - Marquina Leal, Angyela Rocìo (2019)
This investigation was realized by the purpose of analyzing if there is necessary the adoption of legal measures in the predial tax to avoid the prejudice to the verus dominus for duplicity of payments in Peru. In function to it, the following problem of investigation was formulated: there is necessary the adoption of legal measures in the predial tax to avoid the prejudice to the verus dominus for duplicity of payments in Peru?, question that, during the time of investigation, has been confirmed by the hypothesis sustained in the existence of a positive incident in the safeguard of the verus dominus. The investigation is qualitative, of not experimental type and explanatory design Taking form as a sample for 30 juridical materials (Legislation, Jurisprudence, Doctrine, Processes), graphically, virtually and of Web content, the same ones that are considered to author's convenience. The methods were in use exegético, systematicly, inductive - deductive, hermeneutic - juridical, analytical - synthetic, historical method and of the comparison. In that sense, the results indicate that, the adoption of legal measures in the property tax avoids the damage to verus dominus by duplication of payments in Peru, because in the doctrine and in the national legislation itself that, the legal measures, in general, they constitute legal security mechanisms, which can be adopted in order to safeguard the rights of taxpayers, such measures also tend to ensure the payment of an obligation, therefore the hypothesis is accepted. The Municipalities, in accordance with the provisions of the Property Tax Law, must continue with the collection of the Property Tax of all taxpayers, regardless of whether they are considered the owner or holder of a real estate, in order not to ransgress the collection of said tax. Tax whose purpose is for the investment in the execution of public works, to comply with informing that there is more than one taxpayer.